2022
DOI: 10.3390/genes13081341
|View full text |Cite
|
Sign up to set email alerts
|

Brain Proteome-Wide Association Study Identifies Candidate Genes that Regulate Protein Abundance Associated with Post-Traumatic Stress Disorder

Abstract: Although previous genome-wide association studies (GWASs) on post-traumatic stress disorder (PTSD) have identified multiple risk loci, how these loci confer risk of PTSD remains unclear. Through the FUSION pipeline, we integrated two human brain proteome reference datasets (ROS/MAP and Banner) with the PTSD GWAS dataset, respectively, to conduct a proteome-wide association study (PWAS) analysis. Then two transcriptome reference weights (Rnaseq and Splicing) were applied to a transcriptome-wide association stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…We determined that ten genes (PROC, KNG1, THBS2, SERPINA1, RARRES2, GP6, SERPINE2, SERPINA10, EFEMP1, and MSR1) (Supplementary Table 8), implying that these genes could not be significant in GWAS of VTE. These findings are consistent with observations from other PWAS studies that found the novel genes from regions below genome-wide significant P values [32][33][34].…”
Section: Significance Of the Protein Findingssupporting
confidence: 92%
“…We determined that ten genes (PROC, KNG1, THBS2, SERPINA1, RARRES2, GP6, SERPINE2, SERPINA10, EFEMP1, and MSR1) (Supplementary Table 8), implying that these genes could not be significant in GWAS of VTE. These findings are consistent with observations from other PWAS studies that found the novel genes from regions below genome-wide significant P values [32][33][34].…”
Section: Significance Of the Protein Findingssupporting
confidence: 92%
“…De novo mutations associated with ASDs are found in transcription factor 20 (Tcf20) 82 and Tcf20 knockdown mice display impairments in social novelty recognition and pup communication 83 . Moreover, Rbfox1, one of the plasticity genes identified in the enrichment analyses is also linked to risk for ASDs 84 , TRANK1 is a susceptibility gene for bipolar disorder 85 , and RIMS1 was identified in a PTSD TWAS 86 . Together, these findings suggest that TrkB knockdown in the LS decreases expression of genes that control synaptic signaling, which may alter LS function to give rise to behavioral impairments that are relevant for disorders where social communication is affected.…”
Section: Trkb Knockdown In the Ls Regulates Genes Associated With Soc...mentioning
confidence: 99%
“…Another gene, MAP kinase-activating Death Domain protein ( MADD ) showed increased expression with depressive symptom in inhibitory neuron subtype 11 (FDR=0.03). This gene plays a survival-promoting role against TNF mediated apoptosis (33), and it has been found associated with post-traumatic stress disorder (34).…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 29, 2023. ; https://doi.org/10.1101/2023.03.27.23286844 doi: medRxiv preprint Five genes (MADD, TAOK3, SCAI, C11orf58 and CHUK) were both identified by the TWAS and differential expression analysis. MADD plays a survival-promoting role against TNF mediated apoptosis (33), it has been found associated with post-traumatic stress disorder (34). A previous study found individuals suffering from bipolar disorder and schizophrenia showed that a microdeletion that affects TAOK3 (and PEBP1) is present in schizophrenia patients (31), and a GWAS analysis suggested that TAOK3 alone may contribute to neurodevelopmental disorders, at least in schizophrenia (32).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%